Efficacy and Safety of Dexamethasone as an Adjuvant With Bupivacaine and Lignocaine in Supraclavicular Brachial Plexus Block - Hasan, Sanjida; Chowdhury, Ahmed Abu Nasar; Billah, KM Baki; Khatoon, Syeda Nafisa; Rashid, Md Harun Or; Tipu, Md Rezaul Hoque; Barua, Kalyan; Alam, AKM Shamsul (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Perineural injection of corticosteroid has been successfully used to prolong the local anesthetic action. The aim of this study was to evaluation the efficacy and safety of dexamethasone as an adjuvant with bupivacaine-lignocaine in supraclavicular block. Material and methods: This analytical study was carried out in the Department of Anesthesiology in Chittagong Medical College Hospital in collaboration with the Department of Orthopedic Surgery over a period of 22 months starting from January 2012 to December 2014. A total 130 adult patients of either sex with American Society of Anesthesiology (ASA) health status I-II were selected for upper limb surgery under supraclavicular brachial plexus block was randomly allocated in to two groups of 65 patients in each. Group- D was received dexamethasone 2ml (10mg) and Group-C (Control) was received distilled water 2ml in 38ml of bupivacaine and lignocaine with adrenaline (total volume of 40ml). Results: The mean onset of sensory & motor block was 7.72±1.949min & 8.75±2.008min in group-D and 10.49±0.75min & 9.41±0.76 min in group-C. The duration of analgesia in group-D was 11.40±0.844hrs and in group-C was 3.81±0.88hrs. Conclusion: There was significantly prolonged duration of analgesia and better onset of sensory and motor block in dexamethasone group without any unwanted effects. JCMCTA 2018 ; 29 (1) : 47-52